Structural elucidation and in vitro fermentation of extracellular α-d-glucan from Lactobacillus reuteri SK24.003. Issue 2 (October 2015) - Miao, Ming; Ma, Yajun; Jiang, Bo; Cui, Steve W.; Wu, Shengfang; Zhang, Tao
Abstract: The molecular structure and its relationship to in vitro fermentation properties of α-d -glucan from Lactobacillus reuteri SK24.003 were investigated in this study. The chain structure was elucidated by 2D NMR spectroscopy and a possible repeating unit was deduced. During in vitro fecal fermentation, the relatively low initial bacterial population was observed during first 6 h incubation and small increase for α-d -glucan for 12–48 h incubation. A significant decrease in pH (approximately 2.0) was observed for fecal microbiota exposed to α-d -glucan. Acetic acid, propionic acid, n-butyric acid along with total short-chain fatty acid (SCFA) increased upon incubation, andd -glucan was initially fermented well resulting in the higher production of SCFA at 12 h. The n-butyric acid value at 48 h fermentation (1.29 mM) was higher than that of some commercial prebiotic oilosaccharides. These results suggested that α-d -glucan might be efficiently utilized by gut bacteria and may have a positive effect for gastrointestinal health.